Cerebrospinal Fluid Biomarkers of Japanese Encephalitis - Sengupta, Nabonita (F1000Res, 2015)
Japanese encephalitis (JE) is the leading cause of viral encephalitis in Asia. Acute encephalitis syndrome (AES) is a group of central nervous system (CNS) disorders caused by a wide range of viruses, bacteria, fungi, chemicals and toxins. It is important to distinguish between various forms of infectious encephalitis with similar clinical manifestations in order to ensure specific and accurate diagnosis and development of subsequent therapeutic strategies. Cerebrospinal fluid (CSF) is in direct contact with the CNS and hence it is considered to be an excellent source for identifying biomarkers for various neurological disorders. With the recent advancement in proteomic methodologies, the field of biomarker research has received a remarkable boost.  The present study identifies potential biomarkers for JE using a proteomics based approach. The CSF proteomes from ten patients each with JE and Non-JE acute encephalitis were analyzed by 2D gel electrophoresis followed by mass spectrometry. Vitamin D-binding protein (DBP), fibrinogen gamma chain, fibrinogen beta chain, complement C4-B, complement C3 and cytoplasmic actin were found to be significantly elevated in case of JE indicating severe disruption of the blood brain barrier and DBP can be suggested to be an important diagnostic marker.